Extension Forestry in Punjab - Sethi, C. M. (Indian Forester, 1969)
Punjab is predominantly an agricultural State and 76% of its land is under active agriculture which is becoming a very rewarding profession. Its reorganisation during 1966 has left it without any good forests which have mostly gone to Himachal Pradesh. There is acute shortage of all types of wood and most of its cattle-dung is burnt in the hearth. Considerable parts of its southern districts are subjected to severe wind erosion. Unhappily, Punjab has no sufficiently large tracts of land for raising plantations. The paper describes in detail that there is alternatively a great scope and need for Farm Forestry in Punjab which the Punjab Government have resolved to per sue with vigour and determination. It indicates the factors necessary for successful implementation of Extension Forestry and points out the dynamic role that popular Panchayati Raj, institutions and associations like ’Friends of Trees’ with the assistance of trained Foresters can play in securing the willing co-operation of farmers in getting the job done.